Immigration background and the intergenerational correlation in education - Deborah A. Cobb-Clark; Trong-Ha Nguyen (Institute for the Study of Labor (IZA), 2010)
This paper analyzes the degree of intergenerational education mobility among immigrant and native-born youth in Australia. We find that young Australians from non-English-speaking background (NESB) immigrant families have an educational advantage over their English-speaking background (ESB) immigrant and Australian-born peers. Moreover, while highly-educated Australian-born mothers and fathers transfer separate and roughly equal educational advantages to their children, outcomes for ESB (NESB) youth are most closely linked to the educational attainment of their fathers (mothers). On balance, intergenerational mobility in families with two highly-educated parents appears to be much the same for Australian-born and ESB families and is somewhat greater for NESB families. Finally, the greater importance that NESB mothers attribute to education appears to mitigate the educational penalty associated with socio-economic disadvantage.
Keywords: I20; J11; J13; 330; Education; immigration; intergenerational; Bildungsverhalten; Migranten; Familiensoziologie; Bildungsniveau; Mehrsprachigkeit; Schätzung; Australien